Exploring mental health nurses' perceptions on factors contributing to psychiatric readmissions in Eswatini: A qualitative study - Sabelo Bonginkosi Dlamini; Mduduzi Colani Shongwe (Elsevier, 2019)
Background: Since the year 2012, the National Psychiatric Referral Hospital (NPRH) in Eswatini (formerly Swaziland) has recorded high numbers of readmissions of people living with mental illness (PLWMI). The reasons for the observed increase have not been explored. Purpose: We describe the perceptions of mental health nurses on the factors contributing to the increased number of psychiatric readmissions in Eswatini. Methods: A qualitative, exploratory and descriptive design was employed to collect data using an unstructured interview guide through individual in-depth interviews among eleven (11) purposively selected mental health nurses working at the only psychiatric referral hospital in Eswatini. Thematic analysis was conducted following Creswell's steps of qualitative data analysis to generate themes. Results: Majority of the participants (n = 9) held bachelor's degrees in nursing, with an average working experience of seven years in a mental health setting. Eight (8) themes emerged from the data, namely: i) clients' negative attitudes towards medication and the illness, ii) substance abuse, iii) stigma and discrimination, iv) low socio-economic status, v) co-morbidity, vi) lack of family support, vii) family belief system and viii) administrative factors. Conclusion: Mental health nurses perceived comorbidity, clients' negative attitudes, lifestyle habits, as well as social and administrative factors to be major contributors to readmissions of PLWMI. There is need to empower PLWMI with lifestyle-modification measures after discharge in order to prevent future relapses. Advocacy for increased resource allocation for mental health should be intensified in order to curb the number of readmissions among PLWMI. Keywords: Readmissions, Rehospitalizations, Mental health, Mentally ill patients, Psychiatric patients